Moyamoya syndrome in a 6-year-old β-thalassemia major patient: A case report - Maryam Shaukat; Muhammad Aman; Hania Fatima; Faheemullah Khan; Naila Nadeem; Sadaf Altaf; Khabab Abbasher Hussien Mohamed Ahmed (Radiology Case Reports)
Moyamoya disease (MMD) is a rare, chronic cerebrovascular disorder involving progressive bilateral stenosis of the internal carotid artery and its branches, forming abnormal collateral networks that appear as a “puff of smoke” on angiography. While the term MMD is used when the condition is idiopathic, it is called moyamoya syndrome (MMS) when associated with underlying systemic conditions. Reports of MMS with β-thalassemia major are rare, with fewer than 6 cases documented; herein, we report a case of a 6-year-old female, a known case of β-thalassemia major, who exhibited left-sided hemiparesis, revealing radiological and clinical features consistent with MMS. MRI, CTA, EEG, and Echocardiography were used as diagnostic workups to confirm the diagnosis. The patient was treated with hyper-transfusion therapy and pharmacological management, with an ongoing consideration of surgical intervention. The rarity of the occurrence of moyamoya syndrome in β-thalassemia major patients has been discussed, with emphasis on the importance of early recognition and intervention to mitigate neurological complications. This case contributes to the limited literature on β-thalassemia major and MMS occurring together, underscoring the need for heightened clinical awareness and timely management strategies.